“A Syllabus Proposal Based on Information and Communication Technology and the Process Approach for Teaching English Writing”. (2021)
To examine the needs analysis in the Bachelor in English as a Foreign Language, for the design of a skill-based syllabus based on the writing process approach and Information and Communication Technology (ICT) tools to enhance students writing skills.